Optimization of multilayer antireflection coating for solar cells / Norhuda Hamzah - Hamzah, Norhuda (2009)
Photovoltaic is best known as a method for generating solar power by using solar cells packaged in photovoltaic modules, often electrically connected in multiples as solar photovoltaic arrays to convert energy from the sun into electricity. To explain the photovoltaic solar panel more simply, photons from sunlight knock electrons into a higher state of energy, creating electricity.